Correlation of folic acid, vitamin B12 and homocysteine metabolism with lipid levels and inflammatory response in patients with cerebral infarction - Li Ding (Journal of Hainan Medical University, 2017)
Objective: To study the correlation of folic acid, vitamin B12 and homocysteine metabolism with lipid level and inflammatory response in patients with cerebral infarction. Methods: 86 patients with cerebral infarction treated in our hospital between January 2015 and June 2016 were collected as cerebral infarction group and 70 healthy subjects receiving physical examination in our hospital during the same period were selected as normal control group. Immediately after admission, RIA method was used to detect peripheral blood folic acid, Vit12 and Hcy levels; automatic biochemical analyzer was used to determine lipid level; enzymelinked immunosorbent assay (ELISA) was used to detect serum inflammatory factor levels. Results: Serum folic acid and VitB12 levels of cerebral infarction group were lower than those of normal control group while Hcy level was higher than that of normal control group (P<0.05); serum total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C) and apolipoprotein A1 (ApoA1) levels of cerebral infarction group were higher than those of normal control group while high-density lipoprotein cholesterol (HDL-C) level was lower than that of normal control group (P<0.05); serum interleukin-4 (IL-4) and interleukin-10 (IL-10) levels of cerebral infarction group were lower than those of normal control group while interleukin-8 (IL-8), C-reactive protein (CRP) and tumor necrosis factor α (TNF-α) levels were higher than those of normal control group (P<0.05). The Spearman correlation analysis showed that the folic acid, VitB12 and Hcy levels in patients with cerebral infarction were directly correlated with lipid levels and inflammatory response. Conclusions: Folic acid, vitamin B12 and homocysteine metabolism can directly affect the lipid levels and inflammatory response in patients with cerebral infarction, and are the reliable indexes to early judge the disease severity and guide clinical treatment.